1998
DOI: 10.2134/jeq1998.00472425002700050024x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Soil Redistribution in a Small French Watershed as Estimated from Cesium‐137 Data

Abstract: Changes initiated in the 1970s in the agricultural landscape of the north European plains have resulted in increased water erosion. The spatial redistribution of 137Cs was used to assess the magnitude of long‐term soil movements in a 180 ha watershed located in northern France. The 137Cs base level was estimated at 2000 ± 200 Bq m−2. The point data suggest annual soil movements ranging from a loss of 18 Mg ha−1 to a deposition of 19 Mg ha−1. After spatializing these data, it is concluded that 41% of the waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The enrichment ratio was greater than 1·0 for 73 per cent of the storms during the experimental period. This compares with a tracer enrichment ratio for 137 Cs reportedly ranging from 1·1 to 3·0 (Bernard et al, 1998;He and Walling, 1996). Several factors may have contributed to the enrichment ratio exceeding 1·0.…”
mentioning
confidence: 55%
“…The enrichment ratio was greater than 1·0 for 73 per cent of the storms during the experimental period. This compares with a tracer enrichment ratio for 137 Cs reportedly ranging from 1·1 to 3·0 (Bernard et al, 1998;He and Walling, 1996). Several factors may have contributed to the enrichment ratio exceeding 1·0.…”
mentioning
confidence: 55%
“…Besides without spatial variability sampler size should not have an effect. It was reported that the typical CV on reference sites was about 20% (e.g., Sutherland, 1996;Bernard et al, 1998;Basher, 2000;Fornes et al, 2005). For a 20% CV, at least 15 independent samples would be required to estimate 137 Cs reference mean with an allowable .…”
Section: Implicationmentioning
confidence: 99%
“…On reference sites, a 20% coefficient of variation (CV) of 137 Cs inventory was reported typical (Sutherland, 1996;Bernard et al, 1998;Basher, 2000;Fornes et al, 2005;Mabit et al, 2009). For a 20% CV, approximately 11 samples are needed to quantify the reference inventory with an allowable error of 10% at the 90% confidence.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting cultivated soils consist of soils with altered soil profile, with different soil depths, very low organic matter content, very poor structure and low infiltration capacity, which favour erosion processes, and present spatial variability within the plots. All these aspects are not usually taken into account when land transformations are carried out (Bernard et al, 1998;Schoorl and Veldkamp, 2001). Some research carried out in the Mediterranean area points out the influence of these land transformations on changes in the hydrological processes (Alcaraz, 1997; Barthès et al, 1997;Dazzi, Fierotti and Raimondi, 1998;Misopolinos and Zalidis, 2000).…”
Section: Introductionmentioning
confidence: 99%